COACHING UNTUK SUPERVISI AKADEMIK (PENGALAMAN PRAKTIS PENDIDIKAN GURU PENGGERAK) - Riswakhyuningsih, Tri; Susiati, Eva; Wulandari; Duryat; Khusnul Fatekhah, Helmi; Kumariyah (Bapelitbang Kabupaten Batang, 2025)
Coaching for Academic Supervision is the 7th module of 10 modules studied in the education of driving teachers. The purpose of the study is to share coaching experiences for academic supervision. The study was conducted using a qualitative descriptive method. Data sources were coaching modules for academic supervision, independent assignments, group assignments, and reflection journals. Data were collected by reviewing modules, exploring the Learning Management System, and documentation. Data analysis was carried out using triangulation techniques. Learning activities used the flow: starting from oneself, concept exploration, collaboration space, contextual demonstration, elaboration of understanding, connections between materials, and real action. Starting from oneself, reflecting on experiences and feelings when being supervised. Exploration of concepts thinking paradigms and coaching principles, core coaching competencies and TIRTA as the flow of coaching conversations. Collaboration space, practicing coaching conversations with the TIRTA flow. Contextual demonstration, practicing coaching to help develop coachee competencies. Elaboration of understanding, questions and answers and coaching discussions in the realm of academic supervision. Connections between materials, concluding and making reflections. Real action, practicing academic supervision using the coaching thinking paradigm. Keywords: Academic Supervision, Coaching, Leading Teachers, Leading Teacher Education